Imposed benefit sanctions and the unemployment-to-employment transition: the German experience - Kai-Uwe Müller; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the effect of imposed benefit sanctions on the unemployment-to-employment transition of unemployed people entitled to unemployment compensation on the basis of register data from the German Federal Employment Agency. We combine propensity score matching with a discrete-time hazard rate model which accounts for the dynamic nature of the treatment. We find positive short- and long-term effects of benefit sanctions which are robust for men and women in East and West Germany. The effects diminish with the elapsed unemployment duration until a sanction is imposed. The limited use of benefit sanctions can thus be an effective activation tool if they take place not too late in an individual's unemployment spell.
Keywords: J64; J65; H31; 330; benefit sanctions; unemployment transitions; German labor market reform; ex-post evaluation; propensity score matching; hazard rate model; unobserved heterogeneity; Arbeitslosenversicherung; Arbeitsvermittlung; Rechtsdurchsetzung; Wirtschaftspolitische Wirkungsanalyse; Berufliche Integration; Arbeitsuche; Ökonomischer Anreiz; Arbeitslosigkeit; Dauer; Deutschland